TALABALARNING KREDIT-MODUL TIZIMIDA BILIMLARINI BAHOLANISHNING XALQARO TAJRIBASI - Bazarbaeva, A.K. (SCIENCE and SOCIETY, 2022)
This article discusses the international experience of assessing students’ knowledge on the credit-modular system, and the article also includes the basic concept of the credit-module system, the role of the credit-module system in the modern world, and provides brief information about the European credit netting system.